2006
DOI: 10.1126/science.1125317
|View full text |Cite
|
Sign up to set email alerts
|

Stability via Asynchrony in Drosophila Metapopulations with Low Migration Rates

Abstract: Very few experimental studies have examined how migration rate affects metapopulation dynamics and stability. We studied the dynamics of replicate laboratory metapopulations of Drosophila under different migration rates. Low migration stabilized metapopulation dynamics, while promoting unstable subpopulation dynamics, by inducing asynchrony among neighboring subpopulations. High migration synchronized subpopulation dynamics, thereby destabilizing the metapopulations. Contrary to some theoretical predictions, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
174
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(190 citation statements)
references
References 26 publications
(29 reference statements)
14
174
2
Order By: Relevance
“…There are examples of field and laboratory populations with cyclic or more complex dynamics, similar to those generated by the Ricker function, among plants (Crone and Taylor, 1996;Tilman and Wedin, 1991), insects (Dey and Joshi, 2006;Dixon, 10 1990;Hassell et al, 1976;Mueller and Joshi, 2000;Turchin, 2003) and other taxa (Zeng et al, 1998). The Ricker function represents a simple unstructured population model, however, the results presented here indicate that when individual species may have the potential to show stable periodic or more complex dynamics, these may not always be seen in real ecosystems due to interspecific feedback.…”
Section: (I) Differences In R Imentioning
confidence: 99%
“…There are examples of field and laboratory populations with cyclic or more complex dynamics, similar to those generated by the Ricker function, among plants (Crone and Taylor, 1996;Tilman and Wedin, 1991), insects (Dey and Joshi, 2006;Dixon, 10 1990;Hassell et al, 1976;Mueller and Joshi, 2000;Turchin, 2003) and other taxa (Zeng et al, 1998). The Ricker function represents a simple unstructured population model, however, the results presented here indicate that when individual species may have the potential to show stable periodic or more complex dynamics, these may not always be seen in real ecosystems due to interspecific feedback.…”
Section: (I) Differences In R Imentioning
confidence: 99%
“…In contrast, high migration rates are predicted to have the opposite effect of increasing the overall amount of fluctuation in metapopulation size while decreasing the fluctuation in subpopulation size (Dey & Joshi 2006).…”
Section: Introductionmentioning
confidence: 93%
“…For example, migration increased subpopulation synchrony in plants and fruit flies (Molofsky & Ferdy 2005;Dey & Joshi 2006) and increased fluctuations in the size of fruitfly metapopulations (Dey & Joshi 2006). Another study (Ives et al 2004) demonstrated an increase in metapopulation size from migration both theoretically and empirically using a fungus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is within the confines of the interconnected cavities in between soil particles that microorganisms, such as bacteria, interact. Most of our knowledge of population dynamics in such highly structured landscapes comes from a large body of theoretical [5][6][7] and experimental studies [8][9][10][11] concerning macroscopic organisms in macroscopic landscapes. Due to technical challenges, however, experimental study and even a clear theoretical framework of the population dynamics of microorganisms in spatially structured microhabitats such as soil is lacking, especially for interacting bacterial populations such as predator -prey communities.…”
Section: Introductionmentioning
confidence: 99%